Bénéfices et obligations alimentaires dans la belle-famille du couple mixte. Brus et gendres français chez leurs alliés taiwanais - Fong-Ming Yang (Enfances, Familles, Générations, 2012)
Through the context of meals taken in common, this article studies the relationship between the in-laws and the spouse of the couple, in mixed couple situations. The author carried out research with French-Taiwanese couples living in Taiwan, in order to analyze the differentiated commensality (or table-companionship) according to the different status of the French daughters-in-law and sons-in-law (lover, common law partner and spouse) in his Taiwanese family. What emerges from this is that the hospitality, which shows itself by the sharing of the meal between a foreign son-in-law and his in-laws, is rich in symbolic, material, and emotional meaning.